2010
DOI: 10.1136/ip.2010.029215.62
|View full text |Cite
|
Sign up to set email alerts
|

The role of pupils liaisons on traffic penalties and road traffic injuries in Iran

Abstract: Objective The role of pupils liaisons education on social discipline promotion and road traffi c injury prevention was the main objective of this study. Methods It was a before-after interventional study on 2800 pupils randomly selected from six different districts of Tehran. Data was collected by a questionnaire for children's performances and other demographic information. Validity and reliability of questionnaire was determined by content validity and test re test. Results Subjects were 2800 pupils 8-15 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Such a system with the characteristics noted can manage and mediate the tra c and transport initiatives among different organizations in a comprehensive manner. In Iran, like a majority of developing countries, although limited trainings on tra c principles such as Police Aid Program (PAP) are conducted at schools (56), there is almost no credible and formal training program on tra c safety at schools and universities. Limitations of this study were di cult access to participants and gain their con dence to participate in the study.…”
Section: -Weakness In Law Enforcementmentioning
confidence: 99%
“…Such a system with the characteristics noted can manage and mediate the tra c and transport initiatives among different organizations in a comprehensive manner. In Iran, like a majority of developing countries, although limited trainings on tra c principles such as Police Aid Program (PAP) are conducted at schools (56), there is almost no credible and formal training program on tra c safety at schools and universities. Limitations of this study were di cult access to participants and gain their con dence to participate in the study.…”
Section: -Weakness In Law Enforcementmentioning
confidence: 99%
“…In Iran, Road Traffic Injuries (RTIs) are the leading cause of injuries and the second leading cause of death [1,2]. In recent years, like most of the developing countries, various interventions and programs have been designed and implemented to reduce RTIs [3][4][5][6]. Some of these interventions and programs, including severe treatment with speeding, violations, improvements to vehicle safety, and raised fines and penalties, have a moderate impact on reducing the rate and burden of accidents and some of these interventions, such as increased police funding, security of roads, speed cameras, improved emergency medical care services, and development of transportation infrastructures, especially for the rail transportation, have a slight impact on reduction of traffic accidents [7].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies in Iran has shown that, despite the implementation of specific laws such as the use of seat belts, the rate of deaths has had small decline without education, demonstrating the need for education and cultural development in the country [5,15].…”
Section: Introductionmentioning
confidence: 99%